Modeling Hybrid Cars Adoption Using An Extended Version Of The Theory Of Planned Behaviour - P Karuppiah, Vinayagan (2023)
Malaysian environmental issues produced by conventional cars have long been a subject of concern, and must be addressed by consumers’ adoption of hybrid cars. As a result, the purpose of this study is to identify significant factors influencing consumers' intentions to purchase hybrid cars in Malaysia. Identifying key factors influencing purchase intention will assist hybrid car stakeholders in developing strategies to increase consumers' intention to purchase the vehicles. Following that, theory of planned behaviour was employed as a base theory, with two supporting theories, self-identity and self-congruity, to aid in the development of the framework. In total, six independent variables were included in the framework: attitude, subjective norms, perceived behavioural control, environmental concern, price sensitivity and self-identity. Among these independent variables, attitude was used as a mediator, with price sensitivity as a key moderator and purchase intention as a dependent variable also included. The survey was disseminated across Malaysia via the online, and the data with a sample size of 311 were analysed using structural equation modelling (SEM) via smart PLS 3.0. The findings indicate that all independent variables - attitude, subjective norms, perceived behavioural control, self-identity, and environmental concern - have a positive influence on Malaysian consumers' purchase intention. Additionally, it was discovered that attitude plays a significant role in mediating the relationship between environmental concern and purchase intention.